The Influence Of School Well-Being And Optimism On Academic Flow Among High School Students - Marpaung, Ridhona; Setiawati, Farida Agus (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the effect of school well-being and optimism on academic flow among senior high school students. The research is conducted in response to the observation that many students experience boredom, stress, and a lack of engagement in learning, which are characterized by low academic flow. A quantitative survey approach was employed. The population consisted of all 17.690 high school students in Yogyakarta City. The research sample comprised 377 students, selected through purposive sampling from three high schools in Yogyakarta City. The analysis revealed a positive and significant influence of school well-being and optimism on academic flow. Notably, three dimensions of school well-being, having, loving, and health, demonstrated significant effects on academic flow. The having dimension yielded a significance value of 0.003 (0.05), the loving dimension 0.001 (0.05), and the health dimension 0.000 (0.05), indicating that all three contribute significantly to academic flow. Conversely, the being dimension showed no significant effect, with a significance value of 0.717 (0.05). Furthermore, optimism also significantly affected academic flow, with a significance value of 0.000 (0.05). These findings suggest that well-being and optimism are essential to enhancing optimal learning experiences and academic flow among high school students.